Pelatihan Pengolahan Limbah Berbasis Zero Waste pada Kelompok Remaja Desa Kerta, Payangan - Desak Putu Citra Udiyani; Pande Ayu Naya Kasih Permatananda; I Gede Suranaya Pandit (Universitas Katolik Widya Karya Malang, 2023)
Kerta Village is one of the villages located in Gianyar Regency. Along with the development of Kerta Village, currently Kerta Village already has a Waste Management Site (TPS). However, waste management in Kerta Village is not yet optimal. People still like to throw garbage carelessly and do not know how to handle waste, especially household domestic waste. This zero waste-based waste management training was held at the Penyabangan Banjar Hall, Kerta Village, Payangan District, Gianyar with the target being teenagers. The material presented to partners includes socialization of the concept of zero waste in waste management, counseling and training on waste segregation, training and demonstrations on making eco enzymes, and ends with a discussion or question and answer session. Waste management training activities for youth groups in Kerta Village were successfully carried out smoothly and were able to increase youth knowledge about waste management. Through this activity, youth are expected to become agents of change in creating a healthy and environment caring society that is sustainable.